2018
DOI: 10.1007/s11427-017-9191-1
|View full text |Cite
|
Sign up to set email alerts
|

BCI induces apoptosis via generation of reactive oxygen species and activation of intrinsic mitochondrial pathway in H1299 lung cancer cells

Abstract: The compound (E)-2-benzylidene-3-(cyclohexylamino)-2,3-dihydro-1H-inden-1-one (BCI) is known as an inhibitor of dual specific phosphatase 1/6 and mitogen-activated protein kinase. However, its precise anti-lung cancer mechanism remains unknown. In this study, the effects of BCI on the viability of non-small cell lung cancer cell lines NCI-H1299, A549, and NCI-H460 were evaluated. We confirmed that BCI significantly inhibited the viability of p53(-) NCI-H1299 cells as compared to NCI-H460 and A549 cells, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The apoptotic percentage of H460 cells reached 3.72 ± 0.98% with phycocyanin treatment, which was significantly different than that in control cells, but markedly lower than that in H1299 (11.3 ± 0.16%) and LTEP-A2 cells (14.5 ± 0.68%). It is worth noting that Shin et al discovered that (E)-2-benzylidene-3-(cyclohexylamino)-2,3-dihydro-1H-inden-1-one (BCI, an inhibitor of dual specific phosphatase 1/6 and mitogen-activated protein kinase) significantly inhibits the viability of H1299 cells as compared to H460 cells [ 45 ], suggesting that different mechanisms might exist in lung adenocarcinoma (H1299 and LTEP-A2 cells) and undifferentiated large cell lung carcinoma (H460 cells) cell lines. Particularly, the transcription and protein levels of two apoptotic markers (Bcl-2 and Bcl-xL) were not consistently expressed in H460 cells ( Figure 3 ), which further supports the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic percentage of H460 cells reached 3.72 ± 0.98% with phycocyanin treatment, which was significantly different than that in control cells, but markedly lower than that in H1299 (11.3 ± 0.16%) and LTEP-A2 cells (14.5 ± 0.68%). It is worth noting that Shin et al discovered that (E)-2-benzylidene-3-(cyclohexylamino)-2,3-dihydro-1H-inden-1-one (BCI, an inhibitor of dual specific phosphatase 1/6 and mitogen-activated protein kinase) significantly inhibits the viability of H1299 cells as compared to H460 cells [ 45 ], suggesting that different mechanisms might exist in lung adenocarcinoma (H1299 and LTEP-A2 cells) and undifferentiated large cell lung carcinoma (H460 cells) cell lines. Particularly, the transcription and protein levels of two apoptotic markers (Bcl-2 and Bcl-xL) were not consistently expressed in H460 cells ( Figure 3 ), which further supports the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In NCI-H1299 cells, BCl could downregulate the level of Bcl-2 protein and upregulate the Bax protein expression, thereby promoting the release of Cyt-C and activating caspase 8 to trigger apoptosis. 89 …”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…In NCI-H1299 cells, BCl could downregulate the level of Bcl-2 protein and upregulate the Bax protein expression, thereby promoting the release of Cyt-C and activating caspase 8 to trigger apoptosis. 89 McL-1 is an anti-apoptotic protein in the Bcl-2 family proteins, which is essential for the survival of normal cells. It is overexpressed in various cancers, such as lung cancer, colon cancer, multiple myeloma, etc., and is closely associated with poor prognosis.…”
Section: Apoptotic Signaling Pathways In Cancermentioning
confidence: 99%
“…Resulting from cell damage caused by several factors, apoptosis is a widely known cell death mechanism that is initiated by the upregulation of apoptotic protein production [27, 3032]. Researchers have found that increased levels of Bax expression may lead to apoptosis via activation of procaspase-3 [32, 33], whereas others define the pivotal actions of Bcl-2, p-Akt, and p-ERK1/2 on balancing cell survival and death [34, 35]. Suppression of Akt activity within the CNS is linked to post-HI injury-induced neuronal death, demonstrating the importance of the phosphoinositide 3-kinase (PI3K)/Akt pathway as an antiapoptotic mechanism to protect neurons [36].…”
Section: Discussionmentioning
confidence: 99%